Nós dois em nosso ninho entregues ao sabor de amar: o amor romântico nas composições sertanejas universitárias em tempos de fluidez - Araújo, Manuela Aguiar Damião de (2019)
The contemporary theory of the Polish sociologist Zygmunt Bauman (2004), based on the theory of liquidity, was recognized worldwide for studying the actuality as fluid and instantaneous, not only in politics and economics, but also in affective relationships. In contradistinction to his thesis, the compositional sertanejas university writings, in Brazil, have figurativized strong ties when the artists interpret themes more and more linked to the courtship, betrothal and marriage. Starting from this assumption, we chose as primary corpus of research five songs that figure the theme of the strong ties: Vidro Fumê, interpreted by Bruno & Marrone; Cê Topa, played by Luan Santana; Morador de Rua, interpreted by Zé Neto & Cristiano; Folgado, played by Marília Mendonça and Amante não tem lar, performed by Marília Mendonça. The choice was also made from the artists of greatest success in the form of number of access to digital platforms when reproducing their songs. The secondary research corpus, composed of 68 songs, is presented in a reduced form throughout the research in order to complement the debate about the strong affective ties in the Brazilian contemporaneity and, therefore, we established the following hypotheses for this study: a) Compositions university sertanejas divulge solid affective relations in opposition to the theory of liquidity presented a writing of the pain and the lament for telling stories of abandoned men, horns, sufferers legitimizing a Brazilian culture constructed from the relation of power of the man on the woman; b) The "feminine" feminine participation in this aesthetic has deconstructed the model of women legitimized for centuries to figurativizar themes in opposition to the angel woman, submissive and passive and, finally, c) the university sertanejas compositions represent the romantic love a from the moment that couples sing in experiences of marriage and monogamy, for example. For reading these songs, we use Luiz Tatit's concept of figurativization (2014) that analyzes the importance of the inactive units or ways of saying a society at a certain historical moment. As for the theoretical basis, we used the notes of Anthony Giddens (1993) on the transformation of intimacy in contemporaneity as well as the study on affective relationships of the anthropologist Mirian Goldenberg (2001/2010/2013). For the historicization of affections, we discussed with Mary Del Priore (2005/2011), Ronaldo Vainfas (2011), Michele Perrot (2003) and Michel Foucault (1988), among others. Understanding that the universalization of the concept of liquidity in the contemporary world is fragile, this thesis argues that the affective relationships of the Brazilian figurativized in the sertanejas compositions are not totally in line with this proposal.